next up previous
Next: Marginal and conditional distributions Up: Appendix A: Conditional and Previous: Appendix A: Conditional and

Inverse and determinant of partitioned symmetric matrix

Theorem 1

\begin{displaymath}(A+CBD)^{-1}=A^{-1}-A^{-1}C(B^{-1}+DA^{-1}C)^{-1}DA^{-1} \end{displaymath}

Proof:
    $\displaystyle (A+CBD)[A^{-1}-A^{-1}C(B^{-1}+DA^{-1}C)^{-1}DA^{-1}]$  
  $\textstyle =$ $\displaystyle (A+CBD)A^{-1}-(A+CBD)A^{-1}C(B^{-1}+DA^{-1}C)^{-1}DA^{-1}$  
  $\textstyle =$ $\displaystyle I+CBDA^{-1}-(C+CBDA^{-1}C)(B^{-1}+DA^{-1}C)^{-1}DA^{-1}$  
  $\textstyle =$ $\displaystyle I+CBDA^{-1}-CB(B^{-1}+DA^{-1}C)(B^{-1}+DA^{-1}C)^{-1}DA^{-1}$  
  $\textstyle =$ $\displaystyle I+CBDA^{-1}-CBDA^{-1}=I$  

Theorem 2 (inverse of a partitioned symmetric matrix)

Divide an $n\times n$ symmetric matrix $A$ into four blocks

\begin{displaymath}A=\left[ \begin{array}{cc} A_{11} & A_{12}  A_{21} & A_{22}...
...cc} A_{11} & A_{12}  A_{12}^T & A_{22}
\end{array} \right]
\end{displaymath}

The inverse matrix $B=A^{-1}$ can also be divided into four blocks:

\begin{displaymath}B=A^{-1}=\left[ \begin{array}{cc} B_{11} & B_{12}  B_{21} &...
...cc} B_{11} & B_{12}  B_{12}^T & B_{22}
\end{array} \right]
\end{displaymath}

Here we assume the dimensionalities of these blocks are: with $p+q=n$. Then we have

\begin{displaymath}\begin{array}{l}
B_{11}=(A_{11}-A_{12}A_{22}^{-1}A_{12}^T)^{-...
...^{-1}A_{12}(A_{22}-A_{12}^TA_{11}^{-1}A_{12})^{-1}
\end{array}\end{displaymath}

Proof:
$\displaystyle I_n$ $\textstyle =$ $\displaystyle AA^{-1}=AB=\left[\begin{array}{cc}A_{11}&A_{12}  A_{12}^T&A_{22...
...ight]
\left[\begin{array}{cc}B_{11}&B_{12}  B_{12}^T&B_{22}\end{array}\right]$  
  $\textstyle =$ $\displaystyle \left[\begin{array}{cc}A_{11}B_{11}+A_{12}B_{12}^T&A_{11}B_{12}+A...
...22} \end{array}\right]
=\left[\begin{array}{cc}I_p&0  0&I_q\end{array}\right]$  

i.e.,

\begin{displaymath}A_{11}B_{11}+A_{12}B_{12}^T=I_p\;\;\;\;\mbox{or}\;\;\;\;
B_{11}=A_{11}^{-1}-A_{11}^{-1}A_{12}B_{12}^T \end{displaymath}


\begin{displaymath}A_{11}B_{12}+A_{12}B_{22}=0\;\;\;\;\mbox{or}\;\;\;\;
B_{12}=-A_{11}^{-1}A_{12}B_{22} \end{displaymath}


\begin{displaymath}A_{12}^TB_{11}+A_{22}B_{12}^T=0\;\;\;\;\mbox{or}\;\;\;\;
B_{12}^T=-A_{22}^{-1}A_{12}^TB_{11} \end{displaymath}


\begin{displaymath}A_{12}^TB_{12}+A_{22}B_{22}=I_q\;\;\;\;\mbox{or}\;\;\;\;
B_{22}=A_{22}^{-1}-A_{22}^{-1}A_{12}^TB_{12} \end{displaymath}

Plug $B_{12}^T$ into $B_{11}$ to get

\begin{displaymath}B_{11}=A_{11}^{-1}+A_{11}^{-1}A_{12}A_{22}^{-1}A_{12}^TB_{11} \end{displaymath}

or

\begin{displaymath}(I-A_{11}^{-1}A_{12}A_{22}^{-1}A_{12}^T)B_{11}=A_{11}^{-1}
\;\;\;\mbox{or}\;\;\; (A_{11}-A_{12}A_{22}^{-1}A_{12}^T)B_{11}=I_p \end{displaymath}

or

\begin{displaymath}B_{11}=(A_{11}-A_{12}A_{22}^{-1}A_{12}^T)^{-1} \end{displaymath}

Applying theorem 1 to this expression, we also get the other expression in the theorem. Similarly we can get

\begin{displaymath}B_{22}=(A_{22}-A_{12}^TA_{11}^{-1}A_{12})^{-1} \end{displaymath}

and

\begin{displaymath}B_{12}^T=-A_{22}^{-1}A_{12}^T(A_{11}-A_{12}A_{22}^{-1}A_{12}^T)^{-1} \end{displaymath}


\begin{displaymath}B_{12}=-A_{11}^{-1}A_{12}(A_{22}-A_{12}^TA_{11}^{-1}A_{12}^{-1} \end{displaymath}

Theorem 3 (Determinant of a partitioned symmetric matrix)

\begin{displaymath}\vert A\vert=\left\vert \left[\begin{array}{cc}A_{11}&A_{12}\...
...=\vert A_{11}\vert \vert A_{22}-A_{12}^TA_{11}^{-1}A_{12}\vert \end{displaymath}

Proof: Note that
$\displaystyle A=\left[\begin{array}{cc}A_{11}&A_{12}  A_{21}&A_{22}\end{array} \right]$ $\textstyle =$ $\displaystyle \left[\begin{array}{cc}A_{11}&0  A_{12}^T&I \end{array}\right]
...
...c}I&A_{11}^{-1}A_{12}  0&A_{22}-A_{12}^TA_{11}^{-1}A_{12}
\end{array} \right]$  
  $\textstyle =$ $\displaystyle \left[\begin{array}{cc}I&A_{12}  0&A_{22} \end{array}\right]
\l...
...cc}A_{11}-A_{12}A_{22}^{-1}A_{12}^T&0\\
A_{22}^{-1}A_{21}&I\end{array} \right]$  

The theorem is proved as we also know that

\begin{displaymath}\vert AB\vert=\vert A\vert\;\vert B\vert \end{displaymath}

and

\begin{displaymath}\left\vert \begin{array}{cc}B&0 C&D\end{array} \right\vert=...
...cc}B&C 0&D\end{array} \right\vert=\vert B\vert\;\vert D\vert \end{displaymath}


next up previous
Next: Marginal and conditional distributions Up: Appendix A: Conditional and Previous: Appendix A: Conditional and
Ruye Wang 2006-11-14